Religion, Conflict and Peacemaking - Uzma Naz (South Asian Journal of Religion and Philosophy (SAJRP), 2022)
This article explores the reluctance or unwillingness of modern society to cross the boundaries that have been fixed for religion and politics. Many contemporary civilizations keep religion apart from politics and from all forms of government. A more primordial way of thinking, however, claims that a fundamental relationship between religion and politics remains in effect even in societies where there is no close connection between them. The primordial approach considers ethnicity and religious belonging to be the determining characteristics of communities and individuals. The new awareness of religious plurality evident in the contemporary world has enabled various methods of interreligious dialogue to become instruments of peacemaking.